Shiʻi scholars of nineteenth-century Iraq : - Litvak, Meir (Cambridge University Press, 1998)
The shrine cities of Najaf and Karbala in nineteenth-century Ottoman Iraq were the most important Shi'i centers of learning. In the first in-depth study of the period, Meir Litvak explores the social and political dynamics of these communities and the historical development of Shi'i leadership. In this context, the book not only contributes to the historical debates, but also more broadly to an understanding of modern Shi'ism. It will appeal to historians of the Middle East, Islam, and to students of comparative religion.